Sonographic measurement of normal uterine dimension in nulliparous adults - Basnet, Prabhat; Chhetri, Pramod Kumar; Thapa, Kripesh (Journal of Chitwan Medical College, 2022)
Background: Normal uterine size determination of nulliparous women is very important for the diagnosis of the various uterine pathology. There are different pathologies of uterus but before describing the pathological aspects normal dimension has to be defined. Ultrasound is the first tool for scanning female pelvis pathology. The objective of the study is determining the normal uterine dimension in the nulliparous adults and correlate with the age, height, weight and BMI. Methods: The study was conducted in Department of Radiology and Imaging College of medical sciences, Bharatpur. Patient presenting with any other symptoms than pelvic cause are included in study with age group (15-25years). All ultrasound examinations were performed using Toshiba Aplio 500. A cross-sectional study is conducted among the 49 patients in College of Medical Sciences, Bharatpur, over the period of one year (November 2020 to October 2021). Results: Present study showed the mean length, AP diameter, width and volume of the uterus in nulliparous women between the ages of 15-25years. The mean length is 6.88±0.75cm, mean AP diameter is 3.89±0.44cm, mean width is 4.2±0.50 and mean volume is 61.41±16.96 cc. The present study showed the strong correlation between the weight of the patient and uterine dimension, however there is no significant correlation could be established between the age, height and body mass index of the patients with volume uterine dimension. Conclusions: Normal uterine dimension in Nepalese population is similar to the Nigerian, Scandinavian and Iranian population however the dimensions are smaller than the European population which may be due to the body habitus and genetic factors. There is significant correlation between the weight of patient and volume of the uterus.